Relative Financial Performance of Public Sector Banks - Prasad, K. V. N.; Chari, A. A. (Indian Journal of Finance, 2011)
Financial performance is the key indicator for any business organization. The survival, growth and development of a business depend on profitability, which helps to measure the financial performance of business and indicates how far it has been successful. The present study attempts to analyze the financial performance of public sector banks in India, with the basic objective of examining the growth rate index values for various parameters through overall profitability indices. The variables taken for the study are spread ratios, burden ratios, and profitability ratios. The study brings out the relative financial performance of public sector banks.